Cu-POM type catalyst as well as preparation method and application thereof

By using Cu-POM catalyst to optimize the reaction conditions in ester synthesis, the problems of high cost, complex processes and environmental hazards in ester synthesis are solved, and efficient, low-cost and environmentally friendly ester synthesis effects are achieved.

CN119657225APending Publication Date: 2025-03-21CHINA PHARM UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411872504.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing catalysts have problems such as high cost, complex synthesis processes, and environmental hazards in ester synthesis, making it difficult to achieve efficient, low-cost and environmentally friendly ester synthesis.

Method used

Cu-centered Anderson polyoxygenate (Cu-POM) was used as a catalyst to prepare a Cu-POM catalyst by connecting metal Cu to polyoxygenate, and ester synthesis was performed under optimized reaction conditions.

Benefits of technology

It has achieved high yields in ester synthesis and the suitability of various substrates, low cost, simple process, good environmental protection, conforms to the principle of green environmental protection, and has high industrial application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657225A_ABST
    Figure CN119657225A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and particularly relates to a Cu-POM type catalyst and a preparation method and application thereof. The Cu-POM type catalyst provided by the invention is Anderson type polyoxometallate taking Cu as the center, and the Cu-POM type catalyst is prepared by connecting metal element copper with the polyoxometallate through the steps of oil bath, filtration, crystallization and the like. The Cu-POM prepared by the invention is used as a catalyst for esterification reaction, and has the advantages of low cost, simple synthesis conditions, low toxicity and the like; the catalyst is used for catalyzing ester synthesis, the yield is high, high catalytic efficiency can be achieved, the green and environment-friendly principle is met, meanwhile, Cu-POM has high stability and high activity, and multi-batch recycling can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and specifically relates to a Cu-POM type catalyst and a preparation method and application thereof. Background Art

[0002] As one of the important chemical substances in nature, ester compounds are widely used in food, spices, and medicines. The presence of esters is particularly important in antibiotics. Ester compounds are widely present in various chemical and biological substances. There are many ways to synthesize them, the most common of which is the reaction of carboxylic acids or their derivatives such as acyl chlorides and anhydrides with corresponding alcohols. Traditional methods for synthesizing esters cannot be directly synthesized in one step, and unnecessary by-products will be produced in the process, interfering with the synthesis of the target product and also having a certain impact on the separation of the target product. Therefore, it is of great significance to develop efficient methods for preparing esters.

[0003] As the core element of catalytic reaction, catalyst can save reaction time, optimize reaction conditions, reduce reaction cost, increase reaction yield, etc. At present, many catalytic systems related to the preparation of esters have been reported, including homogeneous and heterogeneous catalytic systems. In homogeneous catalytic systems, active catalysts formed by combining metal elements with organic ligands are used, which mainly include gold, palladium, ruthenium, copper, etc. There are also some reports that use environmentally harmful halogen elements as catalysts for reactions. Although they are highly efficient, they are more harmful to the environment. Metal-based catalysts can often play an efficient catalytic role under the coordination of organic ligands, but the organic ligand components are often complex in structure and expensive, and for some organic ligands, their synthesis conditions are demanding, and they are unstable in the reaction, which have become limiting factors for the large-scale application of homogeneous catalysts. For heterogeneous catalysts, their synthesis process is often cumbersome and the conditions are demanding. Transition metal catalytic systems have higher selectivity and reactivity. Transition metal complexes are supported and coordinated by organic ligands, etc., and organic ligands are expensive, the preparation process is complex, and they are easily affected by external conditions. Therefore, finding new ligands to support coordinated transition metals to form new catalytic systems is of great significance for industrial applications.

[0004] Therefore, it is necessary to develop a new catalyst to effectively avoid the defects of the above methods. Summary of the invention

[0005] Polyoxometalates, also known as polyoxometalates (POMs), are a subset of discrete metal oxygen anion clusters. They are cluster-type compounds composed of heteroatoms and polyatoms through oxygen bridges and have specific structures and compositions. Their sizes vary. They also have functional characteristics in a variety of physical and chemical fields. Some of the polyanions of polyoxometalates are centered on main group heteroatoms, which have a great influence on their properties, including silicon, phosphorus, sulfur, etc. Even some transition metal elements such as iron and cobalt can exist in the polyoxometalate structure in the form of heteroatoms.

[0006] Purpose of the invention: The purpose of the present invention is to provide an Anderson-type polyoxometalate centered on Cu, hereinafter referred to as Cu-POM, in view of the deficiencies in the prior art. The Anderson-type polyoxometalate Cu-POM centered on Cu is prepared by connecting metal Cu with the polyoxometalate. Then, Cu-POM is used as a catalyst and benzaldehyde and methanol are used as templates for the reaction. After determining the optimal reaction conditions, a substrate applicability experiment is carried out. The results show that the obtained product has good yield and applicability characteristics for a variety of substrates. The synthetic product is effectively utilized, which complies with the principle of green environmental protection and has high application value for the industrial application of ester synthesis.

[0007] Technical solution: The purpose of the present invention is achieved through the following technical solution:

[0008] In a first aspect, the present invention provides a Cu-POM type catalyst, wherein the Cu-POM type catalyst is an Anderson type polyoxometalate centered on Cu, and the structural formula of the Cu-POM is: (NH4)2[CuMo6O 18 (OH)6], the structural formula is as follows:

[0009]

[0010] In a second aspect, the present invention also provides a method for preparing the above-mentioned Cu-POM type catalyst, the preparation method comprising the steps of: connecting the metal element ketone with the polyoxometalate, and preparing the crystalline state of the Cu-POM type catalyst by oil bath, filtration and crystallization.

[0011] As a preferred embodiment, the preparation method of the Cu-POM catalyst of the present invention comprises the following steps:

[0012] Step S1, firstly accurately weighing an appropriate amount of polyoxometalate crystals and dissolving them in an appropriate amount of distilled water, stirring them under an oil bath to prepare a polyoxometalate solution;

[0013] Step S2, accurately weighing an appropriate amount of CuSO4 and dissolving it in an appropriate amount of distilled water to prepare a CuSO4 solution;

[0014] Step S3, adding the CuSO4 solution dropwise into the polyoxometalate solution;

[0015] Step S4, continue heating and stirring, and filter the final mixed solution to remove insoluble matter;

[0016] Step S5, taking the clear liquid, adding acetonitrile, standing to precipitate crystals, and collecting the product through steps such as recrystallization, filtration, and drying.

[0017] Further preferably, in step S1, the mass volume ratio of the polyoxometalate crystals to distilled water is 5.25 g:105 mL, and the oil bath temperature is 100°C.

[0018] Further preferably, in step S2, the concentration of the CuSO4 solution is 0.0408 g / mL.

[0019] More preferably, in step S3, the dropping speed is 20 to 30 drops / min.

[0020] More preferably, in step S4, the temperature of the heating and stirring is 100° C., and the stirring time is 1.5 hours. The filtering operation should be performed while hot to filter out insoluble matter.

[0021] More preferably, in step S5, the condition is room temperature 25±2° C., and the standing time is 2 to 3 days.

[0022] In a third aspect, the present invention further provides the use of the above-mentioned Cu-POM catalyst in promoting the formation of esters, that is, provides the use of the Cu-POM catalyst as an esterification reaction catalyst.

[0023] Preferably, in the application described in the third aspect, in addition to using the Cu-POM catalyst as a reaction catalyst, a small amount of potassium chloride can also be added to promote the formation of esters, for example, to increase the yield of methyl benzoate.

[0024] The present invention obtains the Cu-centered Anderson polyoxometalate catalyst Cu-POM by connecting the metal element copper with polyoxometalate, collecting the product through oil bath, filtration and crystallization, etc. Anderson polyoxometalate is one of the types of polyoxometalate, and its application is mainly concentrated in the fields of photocatalysis, magnetism, electrochemistry, etc. Its molecular structure is [Hm(XO6)M6O 18]n-, m=0-6, n=2-8, where M represents polyatoms, with Mo and V being more common. X represents the central atom, which contains more elements, such as early transition metals such as iron, copper, and zirconium. In its structure, 6 (Mo6) are combined in the form of public edges, while surrounding the central group {XO6} to form an octahedral structure, and finally forming a planar structure. It can be divided into two different forms of stereo configurations, α-type and β-type. Among them, the α-body is more common, while the β-body is usually a non-planar curved structure. The α-body can be further subdivided into type A and type B according to the number of protons connected to the central atom. Type A is a non-protonated type, and the central atom is directly connected to 6 oxygen atoms to form an octahedral structure. Type B has 6 protons connected to its central atom, which together with oxygen atoms form an octahedral structure. Oxygen atoms often have different coordination types in Anderson-type polyacid materials. Among them, the oxygen atom that is coordinated with two polyatoms and a central heteroatom at the same time is called "three-bridge oxygen (μ3-O)". There are 6 such oxygen atoms distributed above and below the crystal structure. "Two-bridge oxygen (μ2-O)" refers to the oxygen atom that is combined and coordinated with two polyatoms. There are also 6 such oxygen atoms, distributed between the 6 octahedra of the planar structure. "Terminal oxygen (Ot)" refers to an independent oxygen atom that is combined and coordinated with a polyatom. Each polyatom has two terminal oxygen atoms connected to it, totaling 12. In simple terms, the A / B type is distinguished by whether the μ3-O is protonated. Because of the protonated central atom, the configuration of the polyacid is likely to change. In order to prepare new polyoxometalates, many scholars connect organic ligands to Anderson polyacids. The organic ligands are combined by replacing the terminal oxygen atoms in the polyacid structure. This not only utilizes the catalytic effect of the polyacid, but also utilizes the affinity of the organic ligands and the substrate to achieve the possibility of "1+1>2".

[0025] Compared with precious metal catalysts, the Cu-centered Anderson polyoxometalate catalyst has lower cost, easy product separation and purification, good environmental protection, and easy large-scale application. The Cu-POM prepared by the present invention has the advantages of low cost, simple synthesis conditions, low toxicity, etc. as a catalyst for esterification reaction; the catalyst is used to catalyze ester synthesis with high yield, can achieve high catalytic efficiency, conforms to the principle of green environmental protection, and successfully realizes its application in the catalytic synthesis of ester compounds.

[0026] The Cu-POM prepared by the present invention has stable performance as a catalyst for esterification reaction, good catalytic activity, and is simple to study its performance. It still maintains good reaction activity after recycling. For example, compared with Anderson-type polyoxometalates centered on Fe, the polymetallic salt oxidative esterification reaction prepared by adding metal Cu has stronger catalytic performance and higher yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is the infrared spectrum of the Cu-centered Anderson-type polyacid prepared in Example 1;

[0028] Figure 2 is the infrared spectrum of the Fe-centered Anderson-type polyacid prepared in Example 2;

[0029] Figure 3 NMR of methyl benzoate 1 H spectrum;

[0030] Figure 4 Methyl benzoate NMR 13 C spectrum;

[0031] Figure 5 The NMR of the compound 4-methylbenzoate 1 H spectrum

[0032] Figure 6 The NMR of the compound 4-methylbenzoate 13 C spectrum;

[0033] Figure 7 The NMR of the compound 4-methoxybenzoic acid methyl ester 1 H spectrum

[0034] Figure 8 The NMR of the compound 4-methoxybenzoic acid methyl ester 13 C spectrum;

[0035] Fig. 9 The NMR of the compound 4-chlorobenzoic acid methyl ester 1 H spectrum

[0036] Fig.10 The NMR of the compound 4-chlorobenzoic acid methyl ester 13 C spectrum;

[0037] Fig.11 The NMR of the compound 4-bromobenzoic acid methyl ester 1 H spectrum

[0038] Fig.12 The NMR of the compound 4-bromobenzoic acid methyl ester 13 C spectrum;

[0039] Fig.13 Comparison of infrared spectra before and after the catalyst cycle experiment;

[0040] Fig.14 This is an experiment on catalyst recycling. DETAILED DESCRIPTION

[0041] The technical scheme of the present invention is described in detail below through specific embodiments, but the protection scope of the present invention is not limited to the embodiments. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in the field or the product instructions shall be followed. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels. Ammonium molybdate tetrahydrate: Shanghai Yien Chemical Technology Co., Ltd.;

[0042] Copper sulfate: Xilong Chemical Co., Ltd.; methanol: Shanghai Lingfeng Chemical Reagent Co., Ltd.;

[0043] Ethyl acetate and petroleum ether were purchased from Xilong Scientific Co., Ltd.; potassium chloride was purchased from Nanjing Chemical Reagent Co., Ltd.; p-bromobenzaldehyde, p-chlorobenzaldehyde, p-fluorobenzaldehyde, and cyclohexane formaldehyde were purchased from Shanghai Myrel Biochemical Technology Co., Ltd.;

[0044] Benzaldehyde and p-nitrobenzaldehyde were purchased from Shanghai Bidex Pharmaceutical Technology Co., Ltd.; propanol: Sinopharm Chemical Reagent Co., Ltd.;

[0045] All reagents used were of analytical grade; Terminology explanation: Room temperature has the well-known meaning in the art, generally referring to 25±2°C.

[0046] Example 1 Preparation of Cu-centered Anderson-type polyacids

[0047] The specific implementation steps are as follows: weigh 5.25g (NH4)6Mo7O 24 ·4H2O is dissolved in 105mL of deionized water, stirred and heated in an oil bath at 100°C, which is called solution A. Weigh 1.02g of CuSO4 and dissolve it in 25mL of deionized water, which is called solution B. Add solution B to solution A. The drop rate should not be too fast and should be controlled at 25±1 drops / min. After the addition is completed, continue to heat and stir at 100°C for 1.5 hours, and filter the final mixed solution while it is hot to remove insoluble matter. Take the clear liquid and add excess acetonitrile. Let it stand at room temperature for 48 hours. Blue crystals will precipitate, and the product will be collected through recrystallization, filtration, drying and other steps. The results are shown in the attached figure. Figure 1 shown.

[0048] Example 2 Preparation of Fe-centered Anderson-type polyacids

[0049] The specific implementation steps are as follows: weigh 5.25g (NH4)6Mo7O 24·4H2O was dissolved in 105mL of deionized water, stirred and heated in an oil bath at 100°C, which was called solution A. Weigh 1.3g of Fe2(SO4)3 and dissolve it in 25mL of deionized water, which was called solution B. Solution B was added dropwise to solution A, the addition process was slow, and the pH value was controlled between 4.5 and 6. After the addition was completed, heating and stirring were continued at 100°C for 1.5 hours. The final mixed solution was filtered while hot to remove the insoluble matter. The clear liquid was allowed to stand at room temperature for 48 hours to precipitate white crystals. The crystals were filtered and the product was collected through recrystallization, filtration, drying and other steps. The results are shown in the attached figure. Figure 2 shown.

[0050] Example 3 Preparation of methyl benzoate

[0051] The specific implementation steps are as follows: weigh 152 μL of benzaldehyde and 60 μL of methanol, and add 24 mg of the crystalline product of the Cu-POM catalyst prepared in Example 1 and additives 22.2 mg of KCl, 137 μL of H2O2 and 2.0 mL of acetonitrile as solvent, seal, stir at 80°C for 24 hours, and monitor the progress of the reaction by thin layer chromatography. After the reaction is completed, add saturated brine and ethyl acetate for extraction, repeat the extraction operation three times, and combine the organic layers. The insoluble matter in the aqueous phase is filtered and dried to recover the catalyst, and an appropriate amount of anhydrous sodium sulfate is added to dry it, and silica gel is added to make sand, and the product is separated by column chromatography technology to obtain the desired target product. The results are as follows Figure 3 and Figure 4 shown.

[0052] Example 4 Preparation of methyl 4-methylbenzoate

[0053] The specific implementation steps are as follows: weigh 1.77 mL of p-methylbenzaldehyde and 606 μL of methanol, add 240 mg of the crystal product of the Cu-POM catalyst prepared in Example 1 and 222 mg of potassium chloride, 1.37 mL of 30% H2O2 solution, and 20.0 mL of acetonitrile as solvent, stir at 80°C for 24 hours, and monitor the progress of the reaction by thin layer chromatography; extract the reaction mixture, concentrate the organic layer, and separate and purify it by column chromatography to obtain the target product 4-methylbenzoic acid methyl ester with a yield of 77%. The results are as follows: Figure 5 and Figure 6 shown.

[0054] Example 5 Preparation of methyl 4-methoxybenzoate

[0055] The specific implementation steps are as follows: weigh 1.82mL of p-methoxybenzaldehyde and 606μL of methanol, add 240mg of the crystallized product of the Cu-POM catalyst prepared in Example 1 and 222mg of potassium chloride, 1.37mL of 30% H2O2 solution, and 20.0mL of acetonitrile as solvent, stir at 80°C for 24 hours, and monitor the progress of the reaction by thin layer chromatography. After the reaction mixture is extracted, the organic layer is concentrated and sanded, and separated and purified by column chromatography to obtain the target product 4-methoxybenzoic acid methyl ester with a yield of 77%. The results are as follows Figure 7 and Figure 8 shown.

[0056] Example 6 Preparation of methyl 3-fluorobenzoate

[0057] The specific implementation steps are as follows: weigh 1.58 mL of 3-fluorobenzaldehyde and 606 μL of methanol, add 240 mg of the crystallized product of the Cu-POM catalyst prepared in Example 1 and 222 mg of potassium chloride, 1.37 mL of 30% H2O2 solution, and 20.0 mL of acetonitrile as solvent, stir at 80°C for 24 hours, and monitor the progress of the reaction by thin layer chromatography. After the reaction mixture is extracted, the organic layer is concentrated and sanded, and separated and purified by column chromatography to obtain the target product methyl 3-fluorobenzoate with a yield of 71%.

[0058] Example 7 Preparation of methyl 4-chlorobenzoate

[0059] The specific implementation steps are as follows: weigh 1.77mL 4-chlorobenzaldehyde and 606μL methanol, add 240mg of the crystallized product of the Cu-POM catalyst prepared in Example 1 and 222mg of potassium chloride, 1.37mL 30% H2O2 solution, and 20.0mL acetonitrile as solvent, stir at 80°C for 24 hours, and monitor the progress of the reaction by thin layer chromatography. After the reaction mixture is extracted, the organic layer is concentrated and sanded, and separated and purified by column chromatography to obtain the target product 4-chlorobenzoic acid methyl ester with a yield of 74%. The results are as follows Fig. 9 , Fig.10 shown.

[0060] Example 8 Preparation of methyl 4-bromobenzoate

[0061] The specific implementation steps are as follows: weigh 1.75mL 4-bromobenzaldehyde and 606μL methanol, add 240mg of the crystallized product of the Cu-POM catalyst prepared in Example 1 and 222mg of potassium chloride, 1.37mL 30% H2O2 solution, and 20.0mL acetonitrile as solvent, stir at 80°C for 24 hours, and monitor the progress of the reaction by thin layer chromatography. After the reaction mixture is extracted, the organic layer is concentrated and sanded, and separated and purified by column chromatography to obtain the target product 4-bromobenzoic acid methyl ester with a yield of 80%. The results are as follows Fig.11 , Fig.12 shown.

[0062] Example 9 Preparation of methyl 4-trifluoromethylbenzoate

[0063] The specific implementation steps are as follows: In a clean round-bottom flask, add (15.0mmol, 2.04mL) 3-fluorobenzaldehyde and (606μL) methanol, and at the same time add the corresponding amount of the crystal product of the Cu-POM catalyst prepared in Example 1 (1.5mol%, 240mg) and the additive potassium chloride (1.0eq, 222mg), 30% H2O2 solution (1.37mL), the solvent is 20.0mL acetonitrile, and the reaction mixture is stirred for 24 hours at a temperature of 80°C. During this period, the reaction is monitored by a thin layer chromatography spot plate to ensure that the stirring is stopped after the raw materials are completely consumed. After the reaction mixture is extracted, the organic layer is concentrated and sanded, and separated and purified by column chromatography to obtain the target product 4-trifluoromethylbenzoic acid methyl ester (2.26g) with a yield of 74%.

[0064] Example 10 Preparation of methyl 4-nitrobenzoate

[0065] The specific implementation steps are as follows: In a clean round-bottom flask, add (15.0mmol, 1.51mL) 4-nitrobenzaldehyde and (15.0mmol, 606μL) methanol, and at the same time add the crystallized product of the Cu-POM catalyst prepared in Example 1 (1.5mol%, 240mg) and the additive potassium chloride (1.0eq, 222mg), 30% H2O2 solution (1.37mL), the solvent is 20.0mL acetonitrile, and the reaction mixture is stirred for 24 hours at a temperature of 80°C. During this period, the reaction is monitored by a thin layer chromatography spot plate to ensure that the stirring is stopped after the raw materials are completely consumed. After the reaction mixture is extracted, the organic layer is concentrated and sanded, and separated and purified by column chromatography to obtain the target product 4-nitrobenzoic acid methyl ester (2.06g) with a yield of 76%.

[0066] Test Example 1: Comparative test on reaction condition optimization

[0067] In order to verify the effects of catalysts, additives, the amount of additives, the amount of catalysts, temperature and time at different metal element centers on the catalytic activity of the esterification reaction, methyl benzoate in Example 3 was used as a substrate, and the test was carried out according to the preparation of Example 3 as an example, and single variable experiments were carried out on catalysts, additives, the amount of additives, the amount of catalysts, reaction temperature and reaction time at different metal element centers, respectively, and the settings were as follows:

[0068] Catalysts with different metal element centers include: Cu-POM prepared in Example 1, Fe-POM prepared in Example 2; the amounts of catalysts include: 0.1 mol%, 0.5 mol% and 3.0 mol%; it should be noted that the molar percentage of the catalyst here refers to the percentage of the substrate; different additives include: sodium sulfate, sodium sulfite, sodium chloride, sodium carbonate, sodium bicarbonate, potassium fluoride, potassium bromide, zinc chloride, calcium chloride, magnesium chloride and potassium chloride; the amounts of additives include: 0.1 eq, 0.3 eq; reaction temperatures: 60, 70, 80, 90°C; reaction times: 12, 24, 36, 48 h.

[0069] The results show that when the temperature is 80℃, 152μL benzaldehyde, 60μL methanol, the reaction time is 24h, and 137μL H2O2, 22.2mg KCl, 24mg Cu-POM, and 2.0mL acetonitrile are added at the same time, the yield of the prepared ester compounds is higher and the efficiency of the catalytic reaction is higher.

[0070] Test Example 2 Activity of Cu-POM Catalyst

[0071] The specific implementation steps are as follows: Example 3 After the esterification reaction, the aqueous phase is filtered and dried to obtain a solid crude product of Cu-POM catalyst, and then the crude product is washed with ethanol for multiple times and dried for standby use. It is characterized by Fourier transform infrared spectrometer and powder diffraction spectrum. The results show that the structure of the recovered solid catalyst is consistent with that of the catalyst before the reaction. The results are shown in the attached Fig.13 shown.

[0072] At the same time, the amount of reactants in subsequent experiments was adjusted according to the actual amount of catalyst to ensure that the ratio of the amount of reactants to the amount of catalyst remained unchanged to evaluate the reaction yield. The results show that Cu-POM can still maintain good reaction activity after 6 cycles, which also proves the stability and high activity of Anderson-type polyoxometalate catalysts. The results are shown in the attached Fig.14 shown.

[0073] Test Example 3:

[0074] Verification tests were conducted on substances that may play a catalytic role in the reaction. The results are shown in Table 1. The verification process is to first set the reference conditions. This experiment specifically uses the optimal conditions verified in the above-mentioned Experimental Example 1 as the reference conditions corresponding to Condition 8 in Table 1, that is, the reference reaction conditions are: benzaldehyde (1.5mmol, 152μL), methanol (1.5mmol, 60μL), H2O2 (3.0eq, 137μL), KCl (0.2eq, 22.2mg), Cu-POM (1.5mol%, 24mg), acetonitrile (2.0mL), 80℃, 24h. First, the catalyst was replaced with ammonium molybdate, the raw material for synthesizing Cu-POM, as shown in condition 1 in the following table. Other conditions did not change, and its yield decreased significantly compared with the yield under standard conditions; in condition 2, the catalyst was replaced with copper sulfate, the raw material for synthesizing Cu-POM. The results showed that its yield also decreased significantly, but compared with condition 1, its yield was slightly higher than that in condition 1, which also shows that metal elements are more active in catalyzing the reaction of benzaldehyde and methanol. In condition 3, two raw materials, ammonium molybdate and copper sulfate, were used together to replace the catalyst. Although the yield decreased significantly, it was higher than the yield of ammonium molybdate and copper sulfate used alone in conditions 1 and 2. This also shows that in the reaction, the interaction between metal elements and ligands is the key factor in promoting the reaction. In condition 4, potassium chloride was removed, and other conditions remained unchanged. The yield showed a certain downward trend, which also shows that potassium chloride played a certain role in promoting the oxidative esterification reaction of benzaldehyde and methanol. However, in conditions 5 and 6, only ammonium molybdate or copper sulfate was added, and the reaction could not proceed. At the same time, in condition 7, the oxidant was replaced with oxygen, and the results showed that the reaction could not proceed. Combining all the experimental results, it was concluded that in the oxidative esterification reaction of benzaldehyde and methanol, the combination of Cu-POM polyoxometalate materials with potassium chloride and hydrogen peroxide was crucial for the formation of the corresponding esters.

[0075] Table 1: Yields under different conditions

[0076]

Claims

1. A Cu-POM catalyst, wherein the Cu-POM catalyst is an Anderson-type polyoxometalate centered on Cu, and the structural formula of the Cu-POM is: (NH4)2[CuMo6O 18 (OH)6].

2. The method for preparing the Cu-POM type catalyst according to claim 1, characterized in that: The preparation method comprises the steps of: connecting the metal element ketone with the polyoxometalate, performing oil bath, filtering and crystallization, and preparing the crystalline state of the Cu-POM type catalyst.

3. The preparation method according to claim 2, characterized in that: The preparation method comprises the following steps: step S1, firstly accurately weighing an appropriate amount of polyoxometalate crystals, dissolving them in an appropriate amount of distilled water, stirring them under an oil bath to prepare a polyoxometalate solution; step S2, accurately weighing an appropriate amount of CuSO4, dissolving them in an appropriate amount of distilled water to prepare a CuSO4 solution; step S3, adding the CuSO4 solution dropwise into the polyoxometalate solution; step S4, continuing heating and stirring, and filtering the final mixed solution to remove insoluble matter; step S5, taking the clear solution, adding acetonitrile, standing, precipitating crystals, and collecting the product through the steps of recrystallization, suction filtration, drying, etc.

4. The preparation method according to claim 3, characterized in that: In step S1, the mass volume ratio of the polyoxometalate crystals to distilled water is 5.25 g:105 mL, and the oil bath temperature is 100°C.

5. The preparation method according to claim 3, characterized in that: In step S2, the concentration of the CuSO4 solution is 0.0408 g / mL.

6. The preparation method according to claim 3, characterized in that: In step S3, the dropping speed is 20 to 30 drops / min.

7. The preparation method according to claim 3, characterized in that: In step S4, the heating and stirring temperature is 100° C., and the stirring time is 1.5 hours.

8. Use of the Cu-POM catalyst according to claim 1 in promoting the production of esters.

9. The use according to claim 8, characterized in that The esters include: methyl benzoate, methyl 4-methylbenzoate, methyl 4-methoxybenzoate, methyl 3-fluorobenzoate, methyl 4-chlorobenzoate, methyl 4-bromobenzoate, methyl 4-trifluoromethylbenzoate, and methyl 4-nitrobenzoate.

10. The use according to claim 8, characterized in that A Cu-POM catalyst is used as a reaction catalyst to promote the formation of esters and potassium chloride is added.

Citation Information

Cited By

  • Copper-tungsten polyoxometallate, preparation method thereof and application of copper-tungsten polyoxometallate in field of agricultural sterilization

    CN121673303A